Frequency of REM sleep behavior disorders in patients with Parkinson’s disease - Janković, Marko; Svetel, Marina; Kostić, Vladimir (Vojnosanitetski pregled, 2015)
Background/Aim. Sleep is prompted by natural cycles of activity in the brain and consists of two basic states: rapid eye movement (REM) sleep and non-rapid eye movement (NREM) sleep. REM sleep behavior disorder (RBD) is characterized by violent motor and vocal behavior during REM sleep which represents dream enactment. The normal loss of muscle tone, with the exception of respiratory, sphincter, extra ocular and middle ear muscles, is absent in patients with RBD. The origin of RBD is frequently unknown, but can be associated with degenerative neurological disorders, such as Parkinson’s disease (PD). PD patients do not necessarily express features of RBD, which is identified in approximately third to a half of them. The aim of this study was to estimate the prevalence of RBD in a cohort of PD patients, as well as to identify risk-factors for its development. Methods. In the period from December 2010 to September 2011 we recruited 97 consecutive PD outpatients, treated in the Institute of Neurology, Clinical Center of Serbia, Belgrade. After establishing the diagnosis, all the patients filled out a specially constructed questionnaire with the following items: actual age, sex, age at disease onset, disease duration, form of the disease, type of treatment, duration of treatment, the presence of constipation, lessening of smell sense, and family history of PD. At entring the study, patients disability was scored using the Unified Parkinson’s Disease Rating Scale (motor part – UPDRS). Cognitive abilities were assessed by the Mini Mental Status Examination (MMSE) scale, and depression symptoms by the 21-item Hamilton Depression Rating Scale (HDRS). The patients with PD were dichotomized to those with and without RBD using the RBD Questionnaire – Hong Kong (RBDQ-HK) in the manner of an interview. Forms of PD, mode of treatment, sex, constipation and family history were investigated using the Fishers χ2 test. Symptoms and treatment duration, the presence of smell disturbances, MMSE score, UPDRS motor score and HDRS score were analyzed by implementation of the Z-test. Actual age and age at disease onset were evaluated by the unpaired t-test. Results. The RBD-positive group contained 15 (15.5%) patients, while in the rest of them (82/97), RBD was not identified (non-RBD group). There was no difference between the two groups considering gender distribution (p = 0.847), age (p = 0.577), age at disease onset (p = 0.141), duration of PD (p = 0.069), family history (p = 0.591), type of initial symptoms (p = 0.899), constipation (p = 0.353), olfaction (p = 0.32) and MMSE scores (p = 0.217). The duration of treatment in the RBD group was longer than in the non-RBD group (9.4 ± 5.3 and 6.3 ± 3.9 years, respectively; p = 0.029), and the UPDRS motor score in the RBD group was higher (19.1 ± 9.4 and 12.7 ± 8.2, respectively; p = 0.013). Also, HDRS scores were higher in patients expressing RBD (10.1 ± 6.0 and 6.4 ± 4.5, respectively; p = 0.019). Conclusion. We found that 15.5% of the consecutive PD patients had RBD, and that the patients with RBD differed from the non-RBD ones regarding duration of treatment, disease and depressive symptoms severity.